A geographic game with intermediate goods - Pontes, José Pedro (2010)
The paper treats a noncooperative game where an upstream firm and two downstream firms select locations in a spatial system made by two asymmetric countries. The location of the upstream firm is indeterminate and it is assigned to the smaller country, in order to avoid triviality of the location problem. The Nash equilibria of locations of the downstream firms is characterized in the parameter space (coefficient of input transactions, transport cost) although not everywhere uniquely. Keeping the degree of technological interdependency high, economic integration, as measured by the decline of transport costs, shifts production from the country where the input is produced to the larger country. In opposition, keeping transport costs low, technical progress, as measured by the intensity of input transactions, shifts production from the large market to the country where the input is produced.